2007
DOI: 10.1682/jrrd.2006.12.0160
|View full text |Cite
|
Sign up to set email alerts
|

Porous composite prosthetic pylon for integration with skin and bone

Abstract: Abstract-This article presents results of the further development and testing of the "skin and bone integrated pylon" (SBIP-1) for percutaneous (through skin) connection of the residual bone with an external limb prosthesis. We investigated a composite structure (called the SBIP-2) made of titanium particles and fine wires using mathematical modeling and mechanical testing. Results showed that the strength of the pylon was comparable with that of anatomical bone. In vitro and in vivo animal studies on 30 rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 39 publications
4
39
0
Order By: Relevance
“…6 ). The cross section of the pylon clearly demonstrated the ingrowth of the soft tissues into the pores of the titanium, that was similar in nature to our previous experiments with non modified pylons [22, 45, 46]. With the non modified pylons (control), following 6 months after surgery we observed the patchy fibrovascular ingrowth ( Fig.…”
Section: Discussionsupporting
confidence: 85%
“…6 ). The cross section of the pylon clearly demonstrated the ingrowth of the soft tissues into the pores of the titanium, that was similar in nature to our previous experiments with non modified pylons [22, 45, 46]. With the non modified pylons (control), following 6 months after surgery we observed the patchy fibrovascular ingrowth ( Fig.…”
Section: Discussionsupporting
confidence: 85%
“… (a) Schematic view of implant with side fins “ 1 ” positioned in precut slot in bone walls “ 2 .” Figure adapted from Pitkin et al [28]. (b) Press-fitting of fin (“ 1 ” in (a) ) to slot in bone wall results in Ilizavov type distraction (red arrows) and compression (blue arrow) due to elastic resistance of bone wall to widening.…”
Section: Figurementioning
confidence: 99%
“…As was shown in a recent review [26], the SBIP is principally distinguished from other systems for DSA because it provides conditions for the ingrowth of skin and bone cells throughout the entire volume of the implant [2728]. Histological analysis demonstrated that the porosity, volume fraction, and pore size in the SBIP implants were conducive for cells to grow throughout the volume of the implant effectively [29].…”
Section: Introductionmentioning
confidence: 99%
“…7), developed for approximation of a composite structure by a homogeneous rod [18]: S=LFπr3 where L is the span, F is the bending force, and r is the radius of the pylon.…”
Section: Resultsmentioning
confidence: 99%
“…The new development compared to previous reports [14, 18] is that the insert is manufactured with a spiral pattern of drilled holes running along the webs in order to make the pylons more permeable for better in-growth of bone and skin cells such that the pylon becomes an integral part of the skeleton.…”
Section: Introductionmentioning
confidence: 99%